Magnetic resonance spectroscopy for quantification of liver iron deposition in hereditary hemochromatosis of a Chinese family: Four case reports. Issue 46 (18th November 2022) - Zhang, Jing; Liu, Kefu; Sun, Yan; Yu, Jiafeng
Abstract : Rationale: Hereditary hemochromatosis (HH) is a major cause of liver iron overload. The gold standard for the diagnosis of liver iron overload is the histopathological analysis of a liver sample collected by biopsy. The biopsy procedure is both invasive and painful and carries some risks of complications. The multi-echo single-voxel magnetic resonance spectroscopy (HISTO) technique can be used for noninvasive, quantitative assessment of liver iron overload. Patient concerns: We report 4 Chinese Han men, who were relatives. Patient A was admitted with diabetes and presented with thrombocytopenia and skin hyperpigmentation. The other patients had no specific clinical presentation. Diagnoses: Patient A was suspected of having iron in the liver on routine magnetic resonance imaging, therefore, further HISTO, laboratory testing, and liver biopsy were performed, which confirmed iron metabolic abnormalities. Furthermore, we identified hepatic iron deposition using HISTO and laboratory testing of his son and 2 brothers. Combined with symptoms, auxiliary examinations, and liver biopsy, HH was considered. Interventions: As the 4 patients had no other discomfort other than patient A who had diabetes, patient A was placed on therapy comprising the insulin pump, acarbose, and platelet booster capsule. Outcomes: After treatment, the diabetic symptoms of patient A improved. The patient and his relatives were regularly followed-up for HH. Lessons: HH should be considered when hepatic iron deposition is suspected by routine magnetic resonance, as the HISTO sequence can quantitate liver iron deposition and leads to a promising diagnosis. HISTO is of great value in familial cases, especially in young patients requiring long-term follow-up.